Eight months of marathon school training reduced blood pressure, systemic vascular resistance and extracellular water volume - Marjatta Pekola-Kiviniemi; Antti J. Tikkakoski; Jenni K. Koskela; Anna Tahvanainen; Satu Mäkelä; Matti Jääskeläinen; Jukka Mustonen; Ilkka H. Pörsti (Scientific Reports)
Abstract The effects of an eight-month marathon school training program on blood pressure (BP) and underlying hemodynamics were examined in 45 participants and 43 controls. Hemodynamics were recorded using whole-body impedance cardiography, radial tonometric pulse wave analysis, and third-finger BP measurements during passive head-up tilt. The mean ages were 40.9 and 42.2 years, and body mass indexes (BMI) 25.1 and 25.8 kg/m2, respectively. Marathon training decreased mean weight (˗1.6 kg), fat percentage (˗2.7%), and BMI (˗0.5 kg/m2) and increased maximal oxygen uptake (+3.2 ml/kg/min) and insulin sensitivity (+0.013 units) (p < 0.03 for all). During head-up tilt, systolic BP and cardiac output decreased, while diastolic BP, heart rate, and systemic vascular resistance (SVR) increased, but training did not affect these posture-induced changes. Initial aortic and third finger systolic/diastolic BP were numerically but not significantly lower in the marathon vs. control group (by 3.4/2.3 and 5.5/4.5 mmHg, respectively, p > 0.075). Final BP values were significantly lower in the marathon group (by 7.2/4.5 and 10.9/10.2 mmHg, respectively, p < 0.01). Marathon training reduced SVR by 167 dyn×s/cm5×m2(p = 0.041), and extracellular water volume by 0.34 L (p = 0.045). To conclude, aerobic exercise training appears to lower BP, a significant cardiovascular risk factor, by reducing SVR and decreasing extracellular water volume.